Conservation Agriculture as a Potential Strategy to Increase Soil Quality in Colombian Agroecosystems - Valentina Ardila-Garcia; Victoria Eugenia Vallejo; Leidy Paola Plazas-Navarro (Ciencia y Tecnología Agropecuaria, 2022)
Conservation Agriculture (CA) has been promoted in many Latin American countries as an alternative to sustainable production management because of its ability to prevent soil degradation, enhance crop productivity, minimize climate change impact, and protect soil biodiversity. The main objective of this paper was to evaluate the effects of CA on Soil Quality (SQ) in five agroecosystems from Cachipay (Cundinamarca): Coffee Crop (CC) chronosequences of (1) 5 (CC5) and (2) 10 (CC10) years of establishment; Polyculture Cropping System (PCS) chronosequences of (3) 1 (PCS1) and (4) 6 (PCS6) years, and (5) Fallow (F) systems. A Minimum Data Set (MDS) was determined from principal component analysis. Aggregate stability index, aggregate stability, water holding capacity, geometric mean diameter, electric conductivity, heterotrophic bacterial density, and catalase were finally selected into the MDS and used in the calculation of the Soil Quality Index (SQI). CC5 (0.71), CC10 (0.67), PCS6 (0.66), and PCS1 (0.65) had a higher SQI in the study area than F (0.60). The study demonstrated the positive effect of CA practices based on minimum soil disturbance, lower inputs of agrochemicals, permanent soil organic cover with crop residues, and a diversified cropping system on SQ. The MDS-SQI approach represents a practical, promising, and adequate tool for monitoring SQ in agroecosystems.